Modern Digital Technologies for Monitoring Tuberculosis Adherence - Chauhan, Vikas; Verma, Shubham; Kumar Ray, Pushkar; Kumar Mishra, Satyendra; Chaturvedi, Priya; Khatun, Ayesha; Mishra, Anila (Journal of Neonatal Surgery, 2025)
Tuberculosis (TB) is a persistent contagious disease caused by Mycobacterium tuberculosis which is highly prevalent globally. The bacterial disease can manifest as either pulmonary or extrapulmonary. The timely identification of the disease and initiation of anti-tubercular therapy significantly influences the management and treatment outcome of TB. TB is typically treated with a 6 to 9-month medication regimen requiring strict adherence to the therapy. Medication nonadherence leads to increased hospitalization, disabilities, deaths, reoccurrence of the disease, and antimicrobial resistance. Medication non-adherence is a significant global health concern, especially in TB, several approaches including education, behavior, and the use of digital tools can improve that. This review highlights the features, use, benefits, and limitations of various digital tools such as Video Observed Therapy (VOT), 99-DOTs, Drone Observed therapy system (Dr-OTS), Medication Event Reminder Monitor System (MERM), Bio-ingestible sensors and smart pill bottles used in improving the medication adherence of TB. Digital adherence technology could prove to be an acceptable alternative approach to monitoring and improving TB medication adherence....